(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
A station of Alkanjara river which abducts 700 m from Alkanjara dam was studied. Animals and water samples were collected once a month from December 2017 till January 2018, observation samples were taken through the first three months of 2019. Mollusks were identified for the first time in this station. Phisical and chemical qualities of water were studied and the results were diagrammed. Lymnaea peregra (Lymnaeidae : Basommatophora) classification and some of it,s biocenose characteristics were studied. تمت دراسة محطة من نهر القنجرة تقع قبل مصبه في خزان سد القنجرة بـ 700 متر, وجمعت العينات الحيوانية والمائية بمعدل مرة واحدة شهرياً ولمدة عام من كانون الأول 2017 وحتى كانون الثاني 2018 وتم أخذ عينات للمراقبة خلال الأشهر الثلاثة الأولى من عام 2019 م. تم تحديد الرخويات الموجودة في هذه المحطة لأول مرة وكذلك تمت دراسة الصفات الفيزيائية والكيميائية لمياه المحطة ومثلت النتائج في مخططات بيانية, ودرست الصفات التصنيفية للنوع Lymnaea peregra الموجود في هذه المحطة والذي ينتمي إلى صف بطنيات القدم Gastropoda و تحت صف الرئويات Pulmonata ورتبة قاعدية العينين Basommatophora وفصيلة Lymnaeidae, وتمت دراسة بعض صفات التركيب الحيوي الرخوي في المحطة المدروسة.